1997
DOI: 10.1093/ejo/19.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Collagen synthesis from human PDL cells following orthodontic tooth movement

Abstract: The dynamic remodelling processes in the periodontal ligament (PDL) account for the reaction of PDL cells to different orthodontic force simulations. These occur mostly by degradation and synthesis of collagen types I, III, V, VI, XII and XIV. The purpose of this study was to quantify specific collagen types in the PDL from zones of tension and compression of experimental teeth. Such changes could then be correlated with the processes of orthodontic-stimulated tissue breakdown. Maxillary and mandibular premola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 24 publications
0
44
0
Order By: Relevance
“…35 Interestingly, an increase in collagen synthesis during tooth movement on the compression side also has been documented. 36 At first, the latter might seem contradictory, but it is possible that total collagen turnover is increased at compression sites with a net loss due to an imbalance between synthesis and degradation. It was also suggested that 4% stretching of PDL fibroblasts results in a dramatic increase of type I collagen gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…35 Interestingly, an increase in collagen synthesis during tooth movement on the compression side also has been documented. 36 At first, the latter might seem contradictory, but it is possible that total collagen turnover is increased at compression sites with a net loss due to an imbalance between synthesis and degradation. It was also suggested that 4% stretching of PDL fibroblasts results in a dramatic increase of type I collagen gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that inflammatory cytokines, such as PGE2, IL-1α, IL-1β, IL-6 and TNF-α, are produced by mechanically stimulated PDL cells. [11][12][13] Previous reports showed that PDL cells can participate in osteoclastogenesis but the production of the related cytokines in PDL cells has not been fully characterized. In particular, for M-CSF and IL-1β, their production in mechanically stimulated PDL cells has not been documented.…”
Section: Figmentioning
confidence: 99%
“…12,13 During orthodontic tooth movement, PDL collagen is degraded in the compression region, with altered expression of type I collagen (Col-I) and cytoskeleton of cells. 14,15 Hence, the present study aimed to test the hypothesis that cadherin-11 is expressed in PDLCs and modulates cell morphology and collagen synthesis in PDLCs in response to mechanical stress.…”
Section: Introductionmentioning
confidence: 99%